Maximum sustainable yield of trawl fishery along the south-west coast of India: Bayesian estimation approach - Sathianandan, T.V.; Kuriakose, Somy; Mini, K.G.; Safeena, P. K. (Indian Journal of Fisheries, 2020)
The south-west region of the Indian coast is shared by three maritime states and it contributes nearly 32% to the total marine fish production of the country. Mechanised trawl fishery accounts for 44% of the marine fish harvest in the south-west coast and a number of resources are harvested by trawl nets from this region. An assessment of the trawl fishery to determine sustainable harvest levels for mechanised trawlers in the region was carried out using time series data on annual landings and fishing effort of mechanised trawlers during the period 1990-2015. A Bayesian estimation method for Schaefer model was used for the analysis. Posterior probability densities of parameters of the model, maximum sustainable yield (MSY) and corresponding biomass were obtained through Bayesian estimation for the trawl fishery in south-west coast and the harvest levels were found to be above MSY from 2012 onwards. Forecasts of biomass and fish landings by mechanised trawlers upto 2025 under different levels of fishing effort were also simulated using the model to study the dynamic changes over time. It was found that the numbers of multiday trawlers and single day trawlers operating in this region have to be reduced by 207 and 36 respectively to retain the harvest at sustainable level. Keywords: Bayesian estimation, Biodynamic model, Maximum sustainable yield, Trawl fishery